142 Stereotactic Radiosurgery for Medically and Surgically Refractory Acromegaly: Long-term Rates of Remission and Hypopituitarism. (August 2015) - Sheehan, Jason P.; Lee Vance, Mary; Xu, Zhiyuan; Yen, Chun Po; Schlesinger, David; Dodson, Blair; Lee, Cheng-Chia
Abstract : INTRODUCTION: Acromegaly is a challenging clinical entity. Despite improvements in microsurgery and medical therapy, acromegaly persists or recurs in many patients. We evaluate the long-term results of stereotactic radiosurgery (SRS) for acromegalic patients. METHODS: This was a retrospective study of patients treated with SRS at the University of Virginia; the data were collected from 1989 to 2013. A total of 136 patients underwent SRS for acromegaly. Diagnosis of acromegaly was based on the combination of clinical features and biochemical assessment including to serum growth hormone (GH) level, and age- and sex-matched serum insulin-like growth factor 1 (IGF-1) level. All patients underwent a complete endocrine evaluation, neuroimaging study, and ophthalmic examinations before SRS. Patients who had an OGTT GH of <1.0 ng/mL or normal IGF-1 were considered in remission. Postradiosurgical hypopituitarism was defined as a decrease in one or more hormones below normal. RESULTS: With a median follow-up of 61.5 months, 65.4% of the patients achieved remission. The mean time to remission was 27.5 months. The actuarial remission rates at 2, 4, 6, and 8 years postradiosurgery were 31.7%, 64.5%, 73.4%, and 82.6%, respectively. Significant prognostic factors ( P < .05) for remission included a higher margin radiation dose, higher maximum dose, and lower initial IGF-1 level. New pituitary hormone deficiency occurred in 43 patients (31.6%); 2 patients (1.5%) developed panhypopituitarism. Risk factors for new pituitary hormone deficiency were a margin dose >25 Gy and tumor volume >2.5 mL. Other complications included an adverse radiation effect in 1 patient, visual deterioration in 4, and new oculomotor nerve palsy in 1. CONCLUSION: SRS affords endocrine remission in the majority of acromegalic patients. Delivering a higher radiation dose portends a greater chance of remission. The most common complication after SRS was hypopituitarism, but this occurs in a minority of patients.